2019
DOI: 10.7759/cureus.5303
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Tibial Nerve Schwannoma Presenting as Tarsal Tunnel Syndrome

Abstract: Schwannomas are rare, benign tumors originating in the Schwann cells of the peripheral nervous system. They are most commonly found in the head, neck, and upper extremities, which involve the spinal nerves of the brachial plexus. However, schwannomas of the lower extremities are extremely uncommon, and few studies have reported a schwannoma originating from the posterior tibial nerve. We report on a case of a 71-year old male who presented to our clinic because of left foot and ankle neuritic pain. A nerve tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The usual symptoms begin with ankle pain, swelling, painful walking and plantar foot pain while standing, as well as a burning sensation and numbness. Tarsal tunnel syndrome can be caused by benign tumors -like schwannomas - (Jha et al, 2019), perineural fibrosis, varicosities, osteophytes, traumas and postoperative scarring (Neary et al), while the presence of supernumerary structures at the tarsal tunnel can also lead to this syndrome as well.…”
Section: Discussionmentioning
confidence: 99%
“…The usual symptoms begin with ankle pain, swelling, painful walking and plantar foot pain while standing, as well as a burning sensation and numbness. Tarsal tunnel syndrome can be caused by benign tumors -like schwannomas - (Jha et al, 2019), perineural fibrosis, varicosities, osteophytes, traumas and postoperative scarring (Neary et al), while the presence of supernumerary structures at the tarsal tunnel can also lead to this syndrome as well.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies in the literature reported that schwannomas are common in the anterior and flexor areas of the upper extremities and the posterior aspects of the lower extremities [ 12 , 13 ]. The review of lower extremity schwannoma from 2013 to 2020 is tabulated in [ Table 1 ] [ 10 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A Schwannoma tumour located in the posterior tibial nerve in the tarsal tunnel is extremely rare [1][2][3][4][5][6][7][8][9][10], and hence surgery of this pathology also occurs rarely. Schwannoma within the foot, causing pain syndrome, requires differentiation from Morton's metatarsalgia [11].…”
mentioning
confidence: 99%